Firm-level media news, bank loans, and the role of institutional environments - Jia, Zhehao; Li, Donghui; Shi, Yukun; Xing, Lu (Journal of Corporate Finance, 2023)
Employing an international sample of bank loans from 37 countries, we find that both borrowers' intensive media coverage and positive media sentiment reduce the interest rate spreads on bank loans. In syndicated lending, positive media sentiment increases the likelihood of a non-relationship bank leading or participating in a loan syndicate and decreases the loan share of the lead arranger. Furthermore, we demonstrate that the negative impact of media news on loan spreads is more pronounced in countries with better financial information and governance environments, a higher representation of privately owned media, and lower government control of banks. These findings underscore the significance of media coverage and sentiment in shaping the costs of bank loans worldwide.